STATUS AIR TANAMAN SENGON (Alibizia falcataria (L.) Fosberg) PADA BERBAGAI KONDISI TEMPAT TUMBUH - D. Murdiyarso; Pasril Wahid; Riza Adelia (PERHIMPI (Indonesian Association of Agricultural Meteorology), 1992)
Abstract is available in the full text (pdf format)